(untitled) (African Journal of Biomedical Research, 2024)
Hospital-acquired infections become prevalent and dangerous because they are caused by multiresistant bacteria. In this work, the resistance of some nosocomial bacteria was tested using an antibiotic resistance test; then, three moulds isolated from Roquefort and Camembert cheeses were evaluated for their antibacterial activity. The results showed that all the bacteria were resistant to several antibiotics. The three moulds isolated from the cheeses were identified as Penicillium roqueforti, Penicillium camemberti and Geotrichum candidum. These species demonstrated good antibacterial activity against the tested bacteria, although P. roqueforti performed best. Enterobacter cloacae was the most sensitive to the moulds, and Staphylococcus aureus was the only bacterium that was resistant to all the antibiotics and all three moulds. The in vivo antibacterial activity of P. roqueforti confirmed that this mould was able to treat Escherichia coli and E. cloacae infections in mice. Similar to the in vitro activity, E. cloacae demonstrated the highest in vivo sensitivity to the mould